"I won't publish in Chinese now": Publishing, translation and the non-English speaking academic. Issue 39 (May 2019) - Luo, Na; Hyland, Ken
Abstract: While EAL (English as an additional language) scholars across the world are increasingly under pressure to publish internationally, many are confronted with serious language barriers during the process. A key solution for them is turning to text mediators, and particularly translators. However, the effectiveness of research article manuscript translation remains contested. By presenting the case of a Chinese medical doctor who can hardly write a complete sentence in English but regularly publishes in prestigious international journals, we show the impact and importance of manuscript translation in text mediation practices. We argue that despite its somewhat dubious ethicality and hit-and-miss outcomes, manuscript translation appears to be a viable service for EAL scholars given the right set of circumstances. We believe research on text mediation, including translation, can assist authors and perhaps empower ERPP (English for research and publication purposes) teachers to help students mobilize resources more effectively for English text production in addition to enhancing their individual competence.